2019
DOI: 10.1590/fst.15718
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of Lippia alba (Mill) and Cymbopogon citratus D.C. Stapf. essential oils as natural sanitizers in coriander

Abstract: Essential oils (EOs) are a promising alternative for food preservation and can be used instead of synthetic antimicrobial compounds such as sanitizers, as long as they are efficient and safe. On view of this possibility of use, Lippia alba (Mill) (LAEO) and Cymbopogon citratus D.C. Stapf. (CCEO) essential oils were evaluated as natural antimicrobials and applied into coriander for its biocontrol. The EOs were extracted and their physical properties, total phenolics, cytotoxicity to Artemia salina L. and antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our previous study demonstrated the antioxidant and anti-inflammatory synergistic effects of the complex FHH-CZ (Cho et al, 2021). Studies on the synergistic effect of bioactivity by mixing natural materials have been reported (Ozkan et al, 2021;Park et al, 2021;Lima et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Our previous study demonstrated the antioxidant and anti-inflammatory synergistic effects of the complex FHH-CZ (Cho et al, 2021). Studies on the synergistic effect of bioactivity by mixing natural materials have been reported (Ozkan et al, 2021;Park et al, 2021;Lima et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…de Lima et al (24) studied the biocidal potential of bushy matgrass and lemongrass EOs in aqueous solutions with T20 (0.1%, w/v) against strains of foodborne pathogens and natural microbiota on coriander. Lemongrass EO had the lowest MIC of the two EOs (0.62 μL/mL) against S. aureus, Salmonella Typhimurium, Salmonella Enteritidis, and L. monocytogenes.…”
Section: Efficacy Of Individual Eosmentioning
confidence: 99%
“…LC 50 for EO action front Artemia salina L.According to table 3, the EO of C. citratus presented LC 50 equivalent to 315.12 mg•L -1 , being classified as nontoxic according to the criterion of[22] that standardizes LC 50 ≥ 250 mg•L -1 of the EO as nontoxic. Lima et al[56] evaluated the toxicity of the methanol extract of medicinal plants according to the A. salina toxicity bioassay, found LC 50 equivalent to 704.67 ± 31.44 μg•mL -1 , classifying the methanolic extract of the leaves of C. citratus as nontoxic. Divergentresults were found by Ribeir et al[57] when analyzing the toxicity of EO C. citratus against A. salina in the form of a lethal dose (LD 50 ) quantified in 18.85 (μg•mL -1 ), containing variations in the limits of 13.71 to 26 (μg•mL -1 ).…”
mentioning
confidence: 99%